2018
DOI: 10.1177/1744806918768970
|View full text |Cite
|
Sign up to set email alerts
|

Icariin, a flavonoid with anti-cancer effects, alleviated paclitaxel-induced neuropathic pain in a SIRT1-dependent manner

Abstract: BackgroundOne of the most common side effects of paclitaxel was dosage-dependently painful neuropathy. Various reports indicated that spinal neuroinflammation was involved in paclitaxel-induced neuropathic pain. This study investigated the effect of icariin on paclitaxel-induced neuroinflammation and peripheral neuropathy in rats.MethodsTwo parts were included in this study. In part one, the effect of icariin on paclitaxel-induced neuropathic pain was investigated. Mechanical thresholds were measured as primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…22,41,42 It has been shown that activated neuroglia in spinal cord produce proinflammatory cytokines. 43,44 Moreover, recent work has shown that PTX interacts with and activates TLR4 in the spinal cord, leading to the activation of the NF-κB signaling pathway and the release of pro-inflammatory cytokines, including IL-1β and TNF-α. 41 The link between spinal TLR4 and the production of central and peripheral inflammatory cytokines could contribute to behavioral hypersensitivity following exposure to chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…22,41,42 It has been shown that activated neuroglia in spinal cord produce proinflammatory cytokines. 43,44 Moreover, recent work has shown that PTX interacts with and activates TLR4 in the spinal cord, leading to the activation of the NF-κB signaling pathway and the release of pro-inflammatory cytokines, including IL-1β and TNF-α. 41 The link between spinal TLR4 and the production of central and peripheral inflammatory cytokines could contribute to behavioral hypersensitivity following exposure to chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous research disclosed that the drug target of ICA might be related to the increase of cAMP/cGMP ratio (ZHU and LOU, 2006). The related researches uncovered that ICA exerted the antitumor functions mainly in inducing apoptosis and differentiation, prohibiting invasion and metastasis, restraining angiogenesis, and reducing toxicity of radiotherapy and chemotherapy (Yang et al, 2015;Gui et al, 2018;Shi et al, 2014). Among these, the mechanism of SPARC involved in tumorigenesis includes inducing differentiation, inhibiting invasion and metastasis, and restraining angiogenesis of cancer cells (Chen et al, 2012;Ma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that HSYA showed neuroprotection through attenuating oxidative stress, inflammatory response, and neural apoptosis (Pei et al, 2017 ). Another study showed that Icariin could be a potential agent for the treatment of paclitaxel-induced neuropathic pain in a SIRT1-dependent manner (Gui et al, 2018 ). Another study suggested that 3,4-DHBA prevented neuronal cell damage by interfering with the increase of Ca 2+ (Ban et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%